1252. A Challenging Burkholderia Outbreak Investigation Across Multiple Units at an Academic Medical Center From June 2017 to February 2018. (26th November 2018) - Greendyke, William; Hill-Ricciuti, Alexandra; Oberhardt, Matthew; Green, Daniel; Wu, Fann; Whittier, Susan; Saiman, Lisa; Furuya, E Yoko
Abstract: Background: Most outbreak investigations involve short-term, geographically localized clusters. However, some organisms can form environmental reservoirs leading to more prolonged, widespread outbreaks. We describe a prolonged outbreak of Burkholderia at our institution. Methods: An epidemiological investigation was conducted. Burkholderia isolates were genotyped using pulsed-field gel electrophoresis (PFGE) and recA gene sequencing. Initial isolates were sent to a national reference laboratory for multilocus sequence typing (MLST). Results: 32 patients on 12 units (see figure) had ≥1 positive culture for Burkholderia from June 2017 to February 2018. 21 had B. cenocepacia (PFGE pattern A, recA allele 365) and 11 had B. cepacia (PFGE pattern C, recA allele 53). MLST revealed that isolates with recA allele 365 were unique compared with previously identified B. cenocepacia strains. Of 32 patients, 28 (88%) had positive respiratory cultures. Of 32 patients, 3 (9%) had bacteremia. Thirty-day mortality was 4/29 (14%). A case–control study did not reveal a common point source. All surveillance cultures from asymptomatic patients were negative ( n = 53). Two of nine sink drains in rooms of cases were positive for an unrelated strain of B. cepacia. Other environmental cultures were negative for Burkholderia ( n = 49). Cases continued despite routine interventions (see figure), with some incident cases detected long after potential exposures. Ventilator/respiratory equipment (V/RE) cleaning was investigated. Multiple V/RE interventions were implemented: (1) ensuring a sterilization process for ventilator temperature probes (used in heated humidification) was occurring; (2) using disposable manometers on contact isolation patients; (3) reinforcing ventilator cleaning, including those in radiology suites after use. Conclusion: No definitive source of the outbreak was found. New cases continued after reinforcement of basic infection control practices, but subsided after focused attention on V/RE cleaning practices. Control of this outbreak was challenging due to the complexity of a prolonged "latency period" for Burkholderia, difficulty identifying reservoirs, and multiple possible modes of transmission, especially for organisms like Burkholderia that can persist on environmental surfaces and equipment. Disclosures: All authors: No reported disclosures.